The Effectiveness of Using Interactive Videos and Leaflets in Increasing Knowledge of Dental and Oral Health in Grade 5 and 6 Elementary School Children at Madrasah Ibtidaiyah Tarbiyatul Athfal - Safrina Hanifah; Siti Nur Riani; Prastiwi Setianingtyas; Umniyati, Helwiah (YARSI Dental Journal, 2023)
Background: Elementary school age children are a group that is vulnerable to dental and oral diseases because they have behaviors or habits that are less supportive of dental health. Prevention efforts to maintain dental and oral health use counseling media in the form of videos and leaflets to increase knowledge about dental and oral health. The videos and leaflets displayed and distributed in this study contain dental and oral health counseling. Islamic teachings oblige every Muslim to seek knowledge from an early age and to maintain physical and spiritual cleanliness and purity, including dental and oral health. Objective: To determine the effectiveness of using videos and leaflets as a media for dental and oral health counseling and their review from the Islamic side. Research Methods: This type of research is quasi-experimental design. The number of respondents in this study were 93 respondents using purposive sampling method. Results: The results of the Paired T-Test test between the pre-test and post-test values ​​of counseling using video media and leaflets showed significant results (p<0.05), and the results of the Independent test between the post-test video scores and post-test leaflets showed inconsistent results. significant (p>0.05). Conclusion: The use of videos and leaflets as media for dental and oral health counseling is effective on dental and oral health knowledge in grade 5-6 Madrasah Ibtidaiyah Tarbiyatul Athfal. The use of videos and leaflets that can increase knowledge of dental and oral health in grade 5-6 elementary school children is an implementation of maqashid sharia related to Hifdz al-aql and Hifdz an-nafs